Health Services Utilization and Associated Factors in Jimma Zone, South West Ethiopia - Girma, Fitsum (Research and Publications Office of Jimma University, 2011)
BACKGROUND: In Ethiopia, utilization of health services remains low and unevenly distributed. To ensure appropriate health care use, we need to understand factors affecting health care use, and the reasons for low levels of utilization among our community. The objective of the study was to assess utilization of health services and associated factors in Jimma zone, south west Ethiopia. METHODS: A cross sectional data was collected from January 15 to February 08, 2007 in Jimma zone. First, four districts were selected by lottery method. Then 2 ‘kebeles’ from each district were selected randomly and households were selected by systematic sampling. A total of 836 households were studied. The data were cleaned, coded and entered into computer and analyzed using SPSS for windows version 12.0. Bivariate analysis and logistic regression were conducted and a significance level of 5% was considered for interpretation. RESULTS: The health services utilization rate was found to be 45.6%. After controlling confounders using logistic regression; sex (OR=0.23), marital status (OR=8.1), household income (OR=0.70), socioeconomic status (OR=3.5), presence of disabling health problem (OR=3.3), presence of an illness episode (OR=28.3), perceived transport cost (OR=3.6), perceived treatment cost (OR=0.15) and distance to the nearest health center or hospital (OR=2.9) were found to be predictors of utilization of health care. CONCLUSION: It has been shown that utilization level was not satisfactory. Thus, we recommend that the level of health service utilization should be improved by improving predictors of health care use like physical accessibility.